The impact of the absence of planning laws on the capacity of the centers of the cities - Mufeed E. Shouk (Wasit Journal of Engineering Sciences)
All Iraqi cities also Erbil city are particularly significant growth since 2005 and so far because of great opening that took place and an increase in rates of economic growth which was reflected in the per capita income and the development of infrastructure and public services. Because of the big shortage in all kinds of service projects, residential and entertainment. decision maker adopting the idea of ​​investing in these areas and to develop and improve the reality after coming out of economic crises caused by wars over the country in general and the events experienced by the city of Irbil, in particular, and for the work and construction, attracting foreign investments had to be set up a facilities to investment firms and investors for the success of  the process decision makers  try to find the laws of planning or change the laws planning in according  to the wishes of investors and to stimulate the investment process and thus develop and improve services and meet the requirements without referring to the main reasons that the laws has set for it.